Endocranial anatomy of Antarctic Eocene stem penguins: implications for sensory system evolution in Sphenisciformes (Aves) - Tambussi, Claudia Patricia; Degrange, Federico Javier; Ksepka, Daniel T. (Journal of Vertebrate Paleontology)
Penguins have a more than 60 million year long evolutionary history. Thus, stem lineage fossil taxa are key to understanding their evolution. Here, we present data on three virtual endocasts from stem penguin skulls collected from the Eocene La Meseta Formation of Seymour Island (Antarctica), along with comparative data from extant penguins and outgroups. These fossils appear to belong to three distinct species, and represent both the oldest (34.2 Ma) and the most basal penguin taxa that have yielded endocast data. Data collected from the fossils provide new support for several important shifts in neuroanatomy and cranial skeletal anatomy along the transition from stem to crown penguins, including (1) caudal expansion of the eminentia sagittalis, (2) an increase in the overlap of the telencephalon onto the cerebellum, (3) reduction of the bulbus olfactorius, and (4) loss of the interaural pathway. The large semicircular canal diameters of the Antarctic fossils as well as the more crownward stem penguin Paraptenodytes antarcticus together suggest that canal size increased in basal penguins relative to outgroup taxa but later decreased near the crown radiation. As in most other wing-propelled diving birds, the endocasts lack evidence of cerebellar folds and possess a relatively large floccular recess. Several aspects of the endocast morphology, including the exposure of the tectum opticum in dorsal view and the rostral displacement of the eminentia sagittalis away from the border of the cerebellum, are seen neither in crown penguins nor in Procellariiformes (the extant sister clade to Sphenisciformes) and so appear to represent unique characters of these stem taxa. Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: ...